Notes about Phaseolus pallar Molina (Leguminosae-Papilionoideae-Phaseoleae): alas but at best a synonym! - Debouck, Daniel G.; Nepi, Chiara (Firenze University Press, 2023)
A name given by Molina in 1782 and again in 1810 to a new Phaseolus species after a food legume crop grown for millennia mostly in the western part of the Quechua realm in South America refers to that crop (in the text of his essay) as well as to a weed (in his short Latin description), thus raising taxonomical uncertainty. Obviously, a taxonomical epithet cannot refer to two different botanical entities within the same genus. An example of that uncertainty was the naming of a specimen likely of Macroptilium lathyroides collected in northern Colombia and kept in the negative series of Berlin-Dahlem at the Field Museum. That crop spread so widely and fast that it received several names that Molina and a fortiori Philippi should have considered.